(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
Gas turbines are motors in which the chemical energy of the fuel is transformed into either mechanical energy of the pipe, or kinetic energy. Gas turbines using shaft power are generators for supplying fossil energy. Gas turbines that transform the fuel energy to kinetic energy are used to drive a thrust producing aircraft. Gas turbines are generators in which the fuel’s chemical energy is transformed into either shaft- or kinetic-load mechanical energy. Gas turbines creating shaft power are generators for generating energy from coal. Turbine technology is built to extract its aim is to extract turbine technology.A gas turbine engine is a device containing many elements of turbomachinery and ancillary subsystems. Air reaches the compressor part that is powered by a portion of the turbine and mounted on the same shaft. Under greater speed, air leaves the compressor and reaches the combustion chamber, where the fuel’s chemical energy is transformed into thermal energy generating exhaust gas under a temperature that correlates to the configuration temperature of the turbine inlet. In the following turbine section the combustion gas spreads, where its overall energy is partly transformed into shaft function and exit kinetic energy. The shaft function is the main part of the energy forms described above for the power generation gas turbines. This includes the total compressor part function needed, bearing frictions, multiple auxiliary subsystems, and the generator. For aircraft gas turbines, a significant part of the overall energy is used to produce high escape kinetic energy, which is necessary for the production of thrust